La historia de la victimología - Guerra Guerra, María Patlova (2024)
Arguably, viclimology has made significan! progress in the second half of the twentieth century. Most of this progress has occurred mainly in industrializad countríes and for that reason, it is reasonable to think thal in the coming years most developing countries may be included, to the extent that they experience greater industrial and social development. It is likely that sorne historians will call the next hundred years: as the "Century far la victim". It Is clear that in the last thirty-five years, victimology and victim assistance have evolved in many countries of the wortd, we can say that many of these developments have been far the efforts of the United Nations, the World Society victimology, leading national programs, such as those developed in the United States, Britain and the Netherlands. lf history has taught us anything it is lhat the situation of victims in the world is finally being recognized and is responding with a variety of support and assistance programs.